Crystallographic study of grain refinement in low and medium carbon steels. Issue 15 (23rd May 2016) - Li, Ming; Li, Jianmin; Qiu, Dong; Zheng, Qing; Wang, Geoff; Zhang, Ming-Xing
Abstract: In order to clarify and articulate the long-standing problems associated with the role of various compounds in grain refinement of as-cast steels, a comprehensive crystallographic study on grain refiners in a number of low carbon steels has been conducted using the edge-to-edge matching (E2EM) model, which has been successfully applied to explain and predict effective grain refiners in light metals. Five commonly investigated compounds, namely NbO, CeS, TiN, Ce2 O3 and TiC, in steels were examined. According to the extent of crystallographic matching, the predicted grain refining potency of these five grain refiners is ranked in the order of NbO > CeS > TiN > Ce2 O3 > TiC, which is consistent with previously reported experimental results. Four different orientation relationships between δ-ferrite and these grain refiners were predicted. One of them has been verified by previously published experimental data. The similarity and the advantages of the E2EM model over conventional Bramfitt's model were also discussed.